Peran Editor Suara.com dalam Menjaga Kredibilitas Berita - Yuyu, Dede; Suryana, Cecep; Dulwahab, Encep (Annaba: Jurnal Ilmu Jurnalistik, 2024)
This research aims to find out the role of editors in maintaining News credibility, which includes three elements based on gatekeeper theory, namely the process of selecting and editing News, controlling and managing News publications, as well as factors that influence editors' decisions in News publications. This research uses gatekeeper theory with a qualitative approach and case study method. The research results show the role of Suara.com editors as gatekeepers to ensure accuracy, balance, relevance and actuality of information in selecting and editing News. Meanwhile, the steps taken in the process of managing and controlling News publications include verifying information, examining viewpoints, and actively monitoring News developments on social media, as well as being proactive in responding to controversial issues. Then Suara.com editors consider factors of social interest, business, editorial approach, social media trends, and reader response in making publication decisions.